2012
DOI: 10.1002/micr.20974
|View full text |Cite
|
Sign up to set email alerts
|

Laser doppler perfusion imaging of skin territory to reflect autonomic functional recovery following sciatic nerve autografting repair in rats

Abstract: Peripheral nerve repair requires comprehensive evaluation of functional outcomes of nerve regeneration; however, autonomic nerve function is seldom evaluated probably due to lack of suitable quantitative methods. This study sought to determine whether autonomic functional recovery could be reflected by cold-induced vasodilation (CIVD) within target skin territory, as monitored by laser Doppler perfusion imaging (LDPI). Rats with sciatic nerve defect injury received autologous nerve grafting, and the plantar su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In the present study, the refinement and reduction of research animals were enforced by using minimal numbers of rats for each experiment, involving experienced and proficient experimenters in rodent surgery, and employing blind approach in data collection. A limitation of the present study is that the vascular physiology of rats may be different to some extent from that in humans, as indicated in our previous studies [7,9]. However, as rodents are the most widely used models in studying neuro-vascular control mechanisms, the findings in the present study have implications in understanding the pathophysiological sequela of peripheral nerve injuries in humans and the development of novel assessment of nerve regeneration in experimental settings [44].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the present study, the refinement and reduction of research animals were enforced by using minimal numbers of rats for each experiment, involving experienced and proficient experimenters in rodent surgery, and employing blind approach in data collection. A limitation of the present study is that the vascular physiology of rats may be different to some extent from that in humans, as indicated in our previous studies [7,9]. However, as rodents are the most widely used models in studying neuro-vascular control mechanisms, the findings in the present study have implications in understanding the pathophysiological sequela of peripheral nerve injuries in humans and the development of novel assessment of nerve regeneration in experimental settings [44].…”
Section: Discussionmentioning
confidence: 88%
“…Vasomotor activities of dermal vasculature in response to local thermal challenges mainly involve neural control mechanisms, including both sympathetic and sensory nerve fibers [1,6]. In previous studies, we found that both baseline blood perfusion and local thermal challengesinduced perfusion change in the skin were altered after peripheral nerve injury [7][8][9]. In rats, transection injury to the sciatic nerve or tibial nerve promptly resulted in a substantial increase in blood perfusion by several fold in ipsilateral plantar skin [8,9], whereas chronically denervated plantar skin did not exhibit a significant difference in blood perfusion as compared to the contralateral normal side [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Another quantification approach involves immunostaining nerve cross sections for neurofilament-200 and viewing with fluorescent microscopy. 18 These diverse methods have been performed successfully and with satisfactory results, but there are disadvantages that exist for each. While random sampling of a nerve cross section can be done relatively inexpensively, the method is time-consuming and the risk of bias still exists.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were then prepared as follows: the specimens were directly immersed into a 2.5% glutaraldehyde/phosphate-buffered saline. They were then processed routinely and embedded in a mixture (Ted Pella Inc., Redding, CA) consisting of 76.0 g Medcast, 18.0 g Araldite 502, 39.0 g dodecenyl succinic anhydride (DDSA), 61.0 g nadic methyl anhydride (NMA), and 2.0 to 3.5% 2,4,6-tri (dimethyl aminomethyl) phenol-30 (DMP-30) by volume. Semithin 0.5 µm transverse sections were cut and stained with toluidine blue.…”
mentioning
confidence: 99%